Malnutrition Is Associated With Impaired Functional Status in Older People Receiving Home Care Nursing Service - Leão, Luana Lemos; Engedal, Knut; Monteiro-Junior, Renato Sobral; Tangen, Gro Gujord; Krogseth, Maria (Frontiers in Nutrition, 2021)
Objective: This study aimed to explore the magnitude and significance of associations to nutritional status in frail older adults receiving assistance from the home care nursing service. Method: In this cross-sectional study, 210 home-dwelling persons 65 years or older who received in-home nursing care service were evaluated. Demographic variables, nutritional status, comorbidities, and the dependency levels of activities of daily living were analyzed. To assess the correlation among the factors that influence nutritional status, a theoretical model was developed and adjusted using the path analysis model. Results: The primary finding is that functional status is directly associated with nutritional status (β=0.32; p<0.001) and severity of comorbidities is indirectly associated with nutritional status (β=-0.07; p<0.017). Conclusion: The elicited outcomes in this study reinforce the concept that nutritional status is linked with functional status in older adults receiving in-home care nursing service.